2008
DOI: 10.1103/physreve.77.036601
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional discretizations of the sine-Gordon equation

Abstract: The method of one-dimensional maps was recently introduced as a means of generating exceptional discretizations of the phi(4) theory, i.e., discrete phi(4) models which support kinks centered at a continuous range of positions relative to the lattice. In this paper, we employ this method to obtain exceptional discretizations of the sine-Gordon equation (i.e., exceptional Frenkel-Kontorova chains). We also use one-dimensional maps to construct a discrete sine-Gordon equation supporting kinks which move with arb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…The nuclear track emulsion technique at the JINR Synchrophasotron began to be used in the 50s with irradiations by 10 GeV protons [32]. Analysis of inelastic interactions of protons with nuclei of NTE composition pointed to the significant role of peripheral interactions.…”
Section: Physics Of Relativistic Nucleimentioning
confidence: 99%
“…The nuclear track emulsion technique at the JINR Synchrophasotron began to be used in the 50s with irradiations by 10 GeV protons [32]. Analysis of inelastic interactions of protons with nuclei of NTE composition pointed to the significant role of peripheral interactions.…”
Section: Physics Of Relativistic Nucleimentioning
confidence: 99%
“…Understanding such properties either on a model-specific basis, or, ideally, based on more general/fundamental principles is an important open direction for these nonlinear dynamical lattices. At this point, we should also mention in passing the very interesting recent work of Barashenkov & van Heerden (2008). There, the examination of exceptional discretizations [bearing an effective translational invariance through the map type approach of Pelinovsky (2006) and Barashenkov et al (2005)] led to some ingenious suggestions on how to discretize so as to preserve genuinely traveling localized excitations i.e., kinks in the discrete sine-Gordon and discrete φ 4 settings.…”
Section: 22mentioning
confidence: 99%
“…A moving discrete kink typically (i.e., in the case of generic discretizations) radiates small-amplitude wave packets losing its energy and being initially decelerated and eventually trapped by the lattice in a well of the PNp [16]. There exist numerous 1 attempts to analyze and reduce the radiation from a moving kink [15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31]. The radiation is attributed to the resonance of moving kinks with small-amplitude phonons.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless it has been shown that the radiation can vanish for a set of selected kink velocities [15,16,20,22,24,25,31]. There exists an example of kink in a non-integrable lattice, radiating no energy while moving with an arbitrary speed [18]. Kink solutions with oscillating background (also known as nanopterons) have been found as permanent profile traveling waves moving with constant velocity [24].…”
Section: Introductionmentioning
confidence: 99%